MODEL KEPEMIMPINAN ETNIS TIONGHOA DI JAWA BARAT (SURVEI PADA PERHIMPUNAN FUQING DI JAWA BARAT) - Mulyani Mulyani (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2016)
The purpose of this research is to developing a leadership model of Tionghoa Ethnic in West Java, through a survey at Fuqing Association in West Java. The study was using a purposive sampling technique in selecting 4 (four) Fuqing Association in West Java, in Bandung, Bogor, Cianjur and Sukabumi. A purposive sampling also applied in selecting respondents. A Collecting Data Technique was using a questionnaires and interviews. An Exploratory Factor Analysis and Confirmatory Factor Analysis were used to analyzing Tionghoa’s Ethnic leadership model in West Java. Exploratory Factor Analysis was used to examine a research model consists of 8 (eight) leadership dimension. A confirmatory factor analysis with partial least square method was used to re-examine a result models. The results of research is a West Java Tionghoa ethnic leadership models, namely Confucius Sunda Leadership Model. A Confucius Sunda Leadership Model describes a charismatic leader figure which protecting, leads people, assisting and encourage his followers to achieve an organization’s vision and mission together. A Confucius Sunda Leadership Model has its contribution in developing a leadership theory.